Low-temperature at booting reduces starch content and yield of wheat by affecting dry matter transportation and starch synthesis - Zhang, Wenjing; Zhang, Anmin; Zhou, Qirui; Fang, Ranran; Zhao, Yan; Li, Zihong; Zhao, Jiawen; Zhao, Mengting; Ma, Shangyu; Fan, Yonghui; Huang, Zhenglai (Frontiers in Plant Science, 2023)
The effects of low-temperature stress (LTS) at booting on grain starch synthesis and yield were examined in two wheat varieties with differing low-temperature sensitivities (insensitive variety Yannong 19 and sensitive variety Wanmai 52). A combination of potted and field planting was employed. For LTS treatment at booting, the wheat plants were placed in a climate chamber for 24 h at −2°C, 0°C or 2°C from 19:00 to 07:00 then 5°C from 07:00 to 19:00. They were then returned to the experimental field. The effects of flag leaf photosynthetic characteristics, the accumulation and distribution of photosynthetic products, enzyme activity related to starch synthesis and relative expression, the starch content, and grain yield were determined. LTS at booting caused a significant reduction in the net photosynthetic rate (Pn), stomatal conductance (Gs), and transpiration rate (Tr) of the flag leaves at filling. The development of starch grains in the endosperm is also hindered, there are obvious equatorial grooves observed on the surface of the A-type starch granules, and a reduction in the number of B-type starch granules. The abundance of 13C in the flag leaves and grains decreased significantly. LTS also caused a significant reduction in translocation amount of pre-anthesis stored dry matte from vegetative organs to grains and amount of post-anthesis transfer of accumulated dry matte into grains, and the distribution rate of dry matter in the grains at maturity. The grain filling time was shortened, and the grain filling rate decreased. A decrease in the activity and relative expression of enzymes related to starch synthesis was also observed, with a decrease in the total starch content. As a result, a decrease in the grain number per panicle and 1000-grain weight were also observed. These findings highlight the underlying physiological cause of decreased starch content and grain weight after LTS in wheat.